1987
DOI: 10.1037/0021-843x.96.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating anxiety and depression: A test of the cognitive content-specificity hypothesis.

Abstract: The development and initial psychometric properties of the Cognition Checklist (CCL), a scale to measure the frequency of automatic thoughts relevant to anxiety and depression, are described in this article. Item analyses of the responses of 618 psychiatric outpatients identified a 14-item depression and a 12-item anxiety subscale that were significantly related, respectively, to the revised Hamilton Rating Scales for Depression and Anxiety. Patients diagnosed according to the Diagnostic and Statistical Manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
384
1
15

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(438 citation statements)
references
References 6 publications
31
384
1
15
Order By: Relevance
“…Clinical studies have shown that stressful life experiences are important etiological factors in the development and maintenance of depression and affective disorders (Kendler et al, 1995(Kendler et al, , 1998Kessler, 1997), particularly associated with cognitive and emotional biases (Beck, 1976;Beck et al, 1987;Coles and Heimberg, 2002;Mathews and Mackintosh, 1998). In the present study, CUS induced cognitive impairments in the AST on the stimulus reversal trials (experiment 1) and on the ED set-shifting task (replicated in both experiments).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown that stressful life experiences are important etiological factors in the development and maintenance of depression and affective disorders (Kendler et al, 1995(Kendler et al, , 1998Kessler, 1997), particularly associated with cognitive and emotional biases (Beck, 1976;Beck et al, 1987;Coles and Heimberg, 2002;Mathews and Mackintosh, 1998). In the present study, CUS induced cognitive impairments in the AST on the stimulus reversal trials (experiment 1) and on the ED set-shifting task (replicated in both experiments).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in such cognitive flexibility are detected on the WCST in human patients with dorsolateral prefrontal cortical lesions (Stuss et al, 2000), and with a variety of neuropsychiatric disorders that involve deficits of mPFC functioning (Fossati et al, 1999;Goldstein et al, 2002). Further, deficits in cognitive flexibility, resulting in perseverative perceptual, emotional, and memory biases have been suggested to be important in depression and anxiety disorders (Beck, 1976;Beck et al, 1987;Coles and Heimberg, 2002;Mathews and Mackintosh, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It has been increasingly recognized that, in addition to mood symptoms, cognitive dysfunction is a major component of depression and anxiety disorders, and may in fact underlie some of the affective symptoms (Beck, 1976;Beck et al, 1987;Coles and Heimberg, 2002;Mathews and Mackintosh, 1998). Patients with anxiety and depression exhibit cognitive and memory biases for emotionally relevant material, particularly with respect to 'controllability' of stressful life events, a concept long theorized to be central to the development of depression (Seligman, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…1 (left panel), the psychopathology and psychotherapy literatures may be relevant. In Beck's Cognitive Model of Depression (Beck, 1963(Beck, ,1967Beck, Brown, Steer, Eidelson, & Riskind, 1987), negative schemas, often referred to as "core beliefs," about the self, the world, and the future become part of a vicious cycle in which neutral and ambiguous situations are interpreted negatively and result in behavioral and affective responses that build and elaborate schemas (Watson, Clark, & Harkness, 1994). In the circumstances following gynecologic cancer treatment, women with negative, conflicted, or weak sexual self schemas would be reluctant to resume intercourse.…”
Section: Schemas Sexuality and Psychological Functioningmentioning
confidence: 99%